Social Studies Learning Applications Based on Science, Technology and Society Approaches in The Contemporary Era - Hasni Hasni; Nana Supriatna; Sapriya Sapriya; Murdiyah Winarti; Moh Said (Social Studies Conference Proceedings, 2022)
This paper is based on the author's analysis that the future trend of developing science and technology requires people willing to learn in an integrative and innovative way. Therefore, social studies education, as the main subject for students in Junior High School, must always be responsive and improve themselves to keep up with the times. This study aims to examine the application of science, technology, and society approaches in social studies learning in junior high schools in the contemporary era. The method uses library research by collecting data from various journals and books relevant to the problem. The discussion method uses a descriptive-analytical method by explaining and elaborating the main ideas related to the problems discussed. Then present, it critically through primary and secondary library sources related to the problem. The results of the study found that the application of the science, technology, and society approach to social studies learning in junior high schools in the contemporary era can be applied in five stages, namely: (1) introduction to the issue of the problem, (2) concept formation, (3) application of concepts in life, (4) consolidation of concepts and (5) assessment. The implication of this research going forward is that it can improve students' competence and problem-solving abilities; for example, technological progress is positive and negative effects on the environment.